Unlearning and undoing modernity-coloniality in an entangled and unravelling world : Toward relational and emergent governance - Sabaheta, Ramcilovic-Suominen; Böhme, Jessica; Ehrnström-Fuentes, Maria (Elsevier, 2026)
This paper explores pathways for unlearning and undoing modernity-coloniality in policy, through a trialogue between scholars drawing from political ontology, relational ontology, and practical eko-philosophy. We argue that conventional mechanistic policymaking fails to address the contemporary metacrises, which we argue require ethico-onto-politico-epistemological shifts from singular worlds to pluriverse. We examine the possibilities and pathways for unlearning and undoing modernity-coloniality in and through policy, asking specifically whether that requires undoing the state and state policy, and what role do predefined policy goals play. Our analysis reveals the need for simultaneous deconstruction of modernist assumptions and reconstruction of relational alternatives. Key pathways include (i) questioning dominant ethico-onto-politico-epistemological assumptions; (ii) reimagining the state as "ontological negotiator"; and (iii) abandoning fixed endpoints for cultivating conditions for pluriversal life-sustaining relations. Our work is inspired by eko-philosophy, Eastern philosophies, and onto-epistemological humility, and embracing of uncertainty as decolonizing methods. We propose "Relational and emergent governance" as a collective organizing arising from deconstructed certainties and reconstructed relationalities—requiring experimental institutions that can maintain relational depth across scales.
Keywords: relational ontology; practical philosophy; decolonial policy; pluriverse; emergent governance; modernity; transformations